Breast cancer in young families: a qualitative interview study of fathers and their role and communication with their children following the diagnosis of maternal breast cancer - Forrest, G; Plumb, C; Ziebland, S; Stein, A (John Wiley & Sons, Ltd., 2009)
Objective: To explore father-child communication following the diagnosis of maternal breast cancer, examine disparities in their understandings of the impact of the illness, and identify gaps in their need for support and information. Methods: The design is the qualitative interview study with thematic analysis. The interviews were home-based with fathers and children in Oxfordshire, UK. The participants were 26 fathers whose partners had early breast cancer and 31 of their children aged between 6 and 18 years. Results: Fathers described graphically their reaction to news of the partner's breast cancer and their attempts to provide support for their partners and maintain normal family life for their children. Fathers were keen to reassure and protect children but often said that they lacked sufficient information about breast cancer - especially side effects of treatments. Fathers sometimes did not recognise the extent of their children's distress and some interpreted their children's reactions as 'bad behaviour' or 'rudeness'. Children were often acutely aware of the father's emotional state, and expressed a wish to protect him. Some fathers would have liked an opportunity to talk to a clinician directly about the children but did not want to claim clinical time for themselves or their children. Conclusion: This study suggests that clinicians could improve their care of breast cancer patients by being more family-centred. Fathers routinely need more information and preparation about the likely impact of the illness and its treatment (especially side effects) on the mother, and how children of different ages may react to the emotional strain. Clinicians need to be prepared to offer to talk to teenagers.